Noahic Covenant in Genesis 9:8-17 and Its Relevance to Global Warming and Flooding in Port Harcourt - Olusakin, Vincent Akinbayo; Asanga, Udeme Bassey (NIU Journal of Humanities, 2025)
The rising spate of flood in the global space majorly attributed to global warming in recent times makes is alarming. The devastations caused by floods cannot but make Christians to wonder if God has reneged on his promise in the Noahic covenant. The problem of this paper therefore, is to examine the validity of the Noahic covenant in Genesis 9:8-17 in relation to the challenges of global warming and flooding in Port Harcourt and the Niger Delta. It aims to investigate the message of the covenant and find out if global warming as well as flooding has invalidated the covenant. In order to foster an understanding of the text and its implication on global warming and flooding, evaluative model of Justin Ukpong is employed. It was found out that the flood in the covenant was not regional, but the floods experienced today are regional. It was also discovered that the flood of Genesis which the covenant refers to, had divine origin, though necessitated by human disobedience, but the contemporary floods, which emanated from the refusal of humans to care for nature as demonstrated in the covenant, is human cause and can be reversed by human adjustment. It is concluded that, as long as flooding does not wipe out the entire creation at a time, Noah’s suzerain has kept his part of the bargain. A deliberate return to creation care to reduce the impact of global warming and deliberate actions by government and other stakeholders to address issues aggravating flooding are therefore recommended.  Keywords: Noahic Covenant, Global Warming, Flood, Port Harcourt, Genesis.